Insulin : Comprehensive review on its Crucial Role in Metabolism and Disease Management - Dr. Rutuja Kumbhar (International Journal of Virus Studies, 2024)
Insulin's pivotal function lies in meticulously regulating blood sugar levels, thus guaranteeing cells access to the necessary energy for optimal functionality. When there is a rise in blood sugar, after a meal, the releases insulin gets released from the pancreas to facilitate the uptake of glucose by cells. Insulin primarily acts on muscle, fat, and liver cells, promoting the uptake of glucose from the blood. Another way to store glucose for later use is as glycogen, which produces energy. Additionally, insulin also a vital role in suppressing the breakdown of stored glycogen and promoting the synthesis of proteins and fats.Glucagon, another hormone produced by the pancreas, works in opposition to insulin. Between the meals or when fasting the blood sugar levels are low. Hence the glucagon signals the lover to release stored glucose, to help maintain the normal blood glucose level. In diabetes mellitus, the body's ability to produce or respond to insulin is impaired, leading to chronically elevated blood sugar levels. This may be harmful to the blood vessels, nerves, and organs, among other things. Insulin therapy is a mainstay of diabetes management, mainly in type 1 diabetes. It may also be used in type 2 diabetes when other treatments are not sufficient to control blood sugar levels.Based on their start, peak, and duration of action, many insulins are available for therapeutic use. These consist of insulins that act quickly, briefly, moderately, and slowly.. Some newer formulations, such as insulin analogs, offer more predictable blood sugar control and fewer side effects compared to traditional insulin.In recent years, advancements in insulin delivery systems, such as insulin pumps and continuous glucose monitors, have also improved the management of diabetes by providing more precise dosing and real-time monitoring of blood sugar levels.
Keywords: Beta cells; Blood glucose or sugar; Insulin; Pancreas; Type 1 DM; Type 2 DM